2022
DOI: 10.1021/acsomega.2c05920
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Covered Copper Catalysts Alter the Reaction Pathway of the Electrochemical CO2 Reduction Reaction

Abstract: The electrochemical CO 2 reduction reaction (CO 2 RR) has attracted considerable attention recently due to the potential conversion of atmospheric CO 2 into useful organic products by utilizing electricity from renewable energy sources. However, the selective formation of desired products only via CO 2 RR has been elusive due to the presence of a myriad of competing reaction pathways, thus calling for effective strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…FEs of C 1 and C 2 products were acquired for the various oxidation states of Cu (Figure 8e); the FE C2 reached as high as 79% ± 2% (52% ± 2% ethylene and 27% ± 1% ethanol) when the average valence of Cu was +0. 35. At the same time, the reduction of CO 2 to methane was suppressed to 0.08%, which enhanced the C 2 selectivity.…”
Section: Non-metal Elementmentioning
confidence: 88%
“…FEs of C 1 and C 2 products were acquired for the various oxidation states of Cu (Figure 8e); the FE C2 reached as high as 79% ± 2% (52% ± 2% ethylene and 27% ± 1% ethanol) when the average valence of Cu was +0. 35. At the same time, the reduction of CO 2 to methane was suppressed to 0.08%, which enhanced the C 2 selectivity.…”
Section: Non-metal Elementmentioning
confidence: 88%
“…25 While ligands blocking surface sites are usually considered to be detrimental to catalysis, an increasing number of reports have indicated that some ligands with appropriate design can also play a positive catalytic role in CO 2 electrolysis. [26][27][28][29][30] The incorporation of such ligands onto catalyst surfaces does not directly introduce alternative active sites, but would create specific reaction microenvironments that can influence the activity and selectivity of CO 2 electrolysis via steric and electronic effects. [26][27][28][29][30] These molecular modifications are expected to control reaction pathways via manipulating electrode hydrophilicity/hydrophobicity, modulating interfacial cation solvation, tuning the adsorption of reaction intermediates, inducing additional chemical activation of CO 2 as well as increasing ion conductivity in MEA electrolyzers.…”
Section: Tailoring Reaction Microenvironments By Molecular Modificationsmentioning
confidence: 99%
“…Converting carbon dioxide (CO 2 ) into valuable chemicals and fuels has made an impact on reducing our carbon footprint. However, the high stability of CO 2 for conversion into different chemicals restricts the application. Therefore, the research community has focused on developing materials and systems for efficient CO 2 conversion by reducing the high activation energy of CO 2 . It is possible to achieve CO 2 reduction via various routes, including photocatalytic and electrochemical conversion. In this way, besides decreasing carbon emissions, value-added chemicals, such as methanol, hydrogen, formic acid, and syngas, can be produced. Among these chemicals, formic acid stands out as an alternative to fossil fuels due to its advantages, such as being an energy-intensive material, having a high volumetric hydrogen density, and having enormous potential as an effective hydrogen storage vector .…”
Section: Introductionmentioning
confidence: 99%